WIFECONTRIBUTIONTO FISHERMAN HOUSEHOLDINCOMEAT WEST BANGLASVILLAGE TEBING TINGGI DISTRICTMERANTI ISLANDRIAU PROVINCE - Lilis Suryani; Hamdi Hamid; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRAKThis studyaims to determinethe increase inhousehold incomeoffishermanthroughfisherman's wife participation to support husband earn a living,sowifecould contribute tohouseholdandreduce economic responsibilities. Thisresearchused survey method is the method through purposive samplingas manyas20fisherman’s wives.The result shows that the fisherman's wife has a significant role insupporting the household economy. Wife's role in support household economicmake wife doing a double role in the household. Fisherman's wife contributethrough such kind of job: rubber tappers, processing of fishery products,fishmonger, daily traders and seamstress. The wife’s contribution was work asrubber tappers, so the conclution was that alternative activities can be developedthrough UMKM (Micro, Small and Medium Enterprises).Keywords : Fisherman wife, houshold income, contribution.